Differential impact of Holder and High Temperature Short Time pasteurization on the dynamic in vitro digestion of human milk in a preterm newborn model. (30th October 2020) - Nebbia, Stefano; Giribaldi, Marzia; Cavallarin, Laura; Bertino, Enrico; Coscia, Alessandra; Briard-Bion, Valérie; Ossemond, Jordane; Henry, Gwénaële; Ménard, Olivia; Dupont, Didier; Deglaire, Amélie
Highlights: Similar protein and lipid digestibility in Holder- (HoP) and HTST-pasteurized human milk. Digestion of HTST-treated human milk caused higher retention of bioactive proteins. Digestion of HTST-treated human milk gave AA release pattern similar to raw HoP milk. Abstract: The high-temperature short-time (HTST, 72 °C, 15 s) pasteurization of human milk (HM) has been proposed as an alternative to the Holder method (HoP, 62.5 °C, 30 min), to increase the preservation of bioactive compounds. We have investigated the impact of HTST and HoP pasteurization on the gastrointestinal kinetics of human milk, using a dynamic in vitro system in a preterm newborn model. An increased protein aggregation on the surface of fat globules following pasteurization, albeit to a lesser extent in HTST than in HoP, was observed. Despite relevant differences in the undigested milk samples, both pasteurization methods led to similar proteolytic patterns, while raw HM presented a higher native lactoferrin content throughout digestion. The slightly decreased amino acid release following HoP, with respect to HTST and raw HM, indicated that peptidomic analysis, which is currently underway, might provide interesting insights on the differential digestive kinetics of differently pasteurized HM.